Fitting Farm Safety into Risk Communications Teaching, Research and Practice - Jim Evans; Scott Heiberger (Journal of Applied Communications, 2015)
New safety challenges are emerging as agriculture evolves within the complexity of serving a growing world population. The nation’s most hazardous industry is struggling to provide safe working environments in the face of demographic changes in the agricultural work force, new technologies, new kinds of enterprises, pushback against regulation, and other forces. Such changes introduce new forms of occupational risk and create greater need for appropriate safety communications. This study examined potentials for improving engagement of the agricultural media, which serve as primary information channels for farmers. Those who teach agricultural communications are key gatekeepers in preparing skilled professional agricultural journalists and other agricultural communicators. Therefore, the study focused on potentials for strengthening skills in farm safety communications through teaching programs in agricultural journalism and communications. The second and related purpose involved advancing understanding of conceptual linkages between farm safety communications and risk communications, using a safety-oriented framework of risk communications. A mixed methods research design involved quantitative and qualitative approaches using an online survey among faculty representatives in 23 agricultural communications programs at universities throughout the nation. Responses identified encouraging potentials and useful direction for integrating farm safety into agricultural communications courses. Findings also shed helpful light on conceptual linkages between risk communications and a seemingly “lost cousin” — farm safety communications. They pointed to new potentials for agricultural communications teaching and scholarship in strengthening connections between theory and practice in risk communications (including farm safety communications) related to agriculture.
Keywords: Farm safety; risk communications; agricultural communications; communications education; courses